Media and communication in Nigeria : conceptual connections, crossroads and constraints - Mutsvairo, Bruce, 1979-; Ekeanyanwu, Nnamdi (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Communications are changing rapidly around the world, but particularly in Africa, where citizens are embracing digital technologies not only to improve interpersonal communication but also the state of their financial well-being. This book investigates these transformations in Nigeria's booming communication industry. The book traces communications in Nigeria back to pre-colonial indigenous communications, through the development of telecommunications, broadcasting networks, the press, the Nigerian film industry ('Nollywood'), and on to the digital era. At a time when Western voices still dominate the academic literature on communication in Africa, this book is noteworthy in drawing almost exclusively on the expertise of Nigerian-based authors, critique the discipline from their own lens, and providing an important contribution to the decolonization of communication studies. The authors provide a holistic analysis of the sector, encompassing print journalism, broadcast journalism, public relations, advertising, film, development communication, organizational communication, and strategic communications. Analysis of the role of digital technologies is woven throughout the book, concluding with a final section theorising the future of communication studies in Nigeria in the light of the digital media revolution. Robust in its theoretical and methodological underpinnings, this book will be an important reference for researchers of Media and Communication Studies, and those working on Africa specifically"--
Introduction: Rethinking Communication Studies in Nigeria: A Methodological and Theoretical Critique / Bruce Mutsvairo and Nnamdi T. Ekeanyanwu -- The Nigerian Media of Communication: History and Fundamental Issues / Nnsikan Senam -- Historical and Contemporary Exploration of the Nigerian Media Landscape: Conventional to Cyberspace Critiques / Godwin Ehiarekhian Oboh -- Appraising the Development of the Nigerian Press: A Historical Analysis of Socio-Political, Economic and Cultural Factors / Aniefiok J Udoudo -- Development and Transformation of the Nigerian Indigenous Communication Media / Barigbon Gbara Nsereka and Belema Papamie -- History and Evolution of National Broadcasting Commission (NBC) / Angela Nkiru Nwammuo and Gloria Nneka Ono -- Nollywood and History of Film-Making in Nigeria: Closing the Gaps in the Narratives / Henry Chibueze Ogaraku -- Probing the Integration of Health Communication in Disciplinary Programs of Nigerian Universities / Chika Euphemia Asogwa and Stephen Afam Kenechukwu -- Evolution of Organizational Communication in Nigeria: From Interpersonal to Digital Communication / Nsikak Solomon Idiong and Iniobong Courage Nda -- The Impact of Digital Technologies in Nigerian Journalism / Ladi S. Adamu -- The Impact of Internet on Content and Journalistic Practices Within Traditional Newspapers in Northern Nigeria / Umar Suleiman Jahun -- Digital Media and the Transformation of Traditional Medical Communication in Nigeria / Abdullahi Saleh Bashir and Herbert E. Batta -- Technologies, Media and the Transmutation of Public Relations and Advertising in Nigerian Societies / Presly Ruke Obukoadata, Ngozi Uduma and Macauley Aniefiok -- The Impact of Digital Technologies on Advertising Practice in Nigeria / Jude M.C. Agbo -- Evolution of Digital Media: Citizen Journalism, Ethics and Self-Censorship in the Nigerian Media Industry / Aniefiok J. Udoudo and Doris A. Nwosu -- Technological Determinism and the Evolution of Nollywood / Ikechukwu Obiaya -- Digitization and the Future of Communication Policy in Nigeria / Sola Adeyanju -- Technological Innovations and the Future of Communication Research and Theories in Nigeria / Pius Owoicho Ogwuche -- The Evolution and Context of Communication Studies in Nigeria / Chuks Odiegwu-Enwerem and Uche Chuks-Enwerem -- Digital Media Revolution and Information Overload in the Nigerian Cyberspace: The Challenges and Prospects / Christopher Ifeakachukwu Ochonogor -- Digital Media and the Future of Development Communication in Nigeria / Josephat I. Okoye.
Keywords: Communication -- Nigeria -- History; Mass media -- Nigeria; Digital media -- Nigeria; LANGUAGE ARTS & DISCIPLINES / Communication